Organizational Behavior Of Organizational Behaviors (Ocb) Through Strengthening The Quality Of Work Life, Professional Commitment, And Personality - et. al., Mikael Ajis, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Teachers' organizational citizenship behaviors is an important element related to the achievement of national education goals and the development of the Indonesian nation as a whole. The initial survey of Organizational citizenhip behaviors (OCB) for temporary teachers of private vocational high schools (SMK) in Sanggau District has not achieved maximum results. Therefore, it is interesting to study the civics behaviors of teachers' organizations. This study aims to determine efforts to improve teacher organizational citizenship behavior by examining the relationship between teacher organizational citizenship behavior and the variables of teacher work life quality, professional commitment and personality. This research uses correlational statistical methods and analysis with the systematic method is carried out. The unit of analysis of the research is non-permanent teachers of private vocational high schools (SMK) in Sanggau Regency, West Kalimantan province with a population of 176 and a sample of 123. The results showed that there was a positive relationship between the quality of work life (QWL) and the behavior of organizational citizens with the strength of the relationship ry1 = 0.98, there is a positive relationship between professional commitment and organizational citizen behaviors (OCB) with strength ry2 = 0.97, and there is a positive relationship between personality and OCB with strength ry3 = 0.861 so that organizational citizen behaviors (OCB) can be improved through quality of life work (QWL), professional commitment and teacher personality. Based on the results of the SITOREM analysis in this study, it can be explained that the priority order of improvements that need to be improved is: 1). Easy to socialize and authoritative, 2). Voluntary action, and; 3). Active in organization. As for the order that is maintained, namely: 1). Work outside the time of duty, 2). Dedication to work, 3). Empathy and avoid problems, 4). Liked, polite and happy to work together, 5). Reliable, 6). Responsible and convey constructive ideas, 7). Calm, focus and confident, 8). Integrity and commitment to career pursuits, 9). Interest in new things, 10). Responsibility for organizational regulations, 11). Professional development and social interaction, 12). Self evaluation and leadership, 13). Be proud of working and building relationships with fellow teachers, 14). Teaches and runs School administration. So it can be concluded that to improve the Organization citizenhip behaviors (OCB), teachers can pay attention to indicators that are not optimal for recommendations and determine the priority order of improvements that need to be made.